Diklat Keterampilan Pembelajaran Berbasis Multimedia untuk Meningkatkan Kompetensi Guru Taman Pendidikan Qur’an - Lilik Sri Hariani; Endah Andayani (Jurnal Pemberdayaan Masyarakat, 2020)
Pesantren "Asy-Syadzili" Pakis Malang currently has both formal and non-formal education which is experiencing rapid growth, marked by the increasing number of students coming from various regions of Java and outside with the number of santri more than 350 people. To organizing the Islamic Boarding School for the Qur'an, Madrasah Diniyah and the Qur'an Education Park, it also organizes junior and senior high school education, but the management is still simple and the majority of Ustadzahs have never attended education or training that supports their duties. The development of increasingly rapid technology, teaching staff must be able to compensate by increasing competence for themselves, so that learning is more fun and meaningful. The strategy developed is the introduction of multimedia-based learning to improve quality, become urgent demands and needs to be done. This training will be attended by all TPQ teachers and TPQ teachers, amounting to 30 people. The impact is that 83.33% of students have begun to understand the concept of multimedia-based learning, 33.33% of clerics have the ability or learning skills using simple mindmapping, 50% of clerics are able to practice the concepts of learning correctly, and 26.67% of clerics are able make a Learning Implementation Plan.